“Efecto de la nutrición translaminar en el comportamiento agronómico del cultivo de banano (musa x paradisiaca Var. Williams) en el cantón Valencia” - Carriel Ortega, Javier Alexander (2020)
The research was carried out in the hacienda "San Carlos de Chillovado", owned by Mr. Carlos Pérez located at kilometer 11 of the enclosure "El Descanso", 1.15 kilometers from the E-30 road of the Valencia highway is located in the northern part of Provincia de los Rios 20 minutes from Quevedo. Four different doses of translaminar fertilizer were used on banana cultivation (Musa x paradisiaca) the time for the development of this work was six months from December 2019 to June 2020. The variables studied in this research were: height of the plant (cm), perimeters of the pseudostem (cm), leaf length (cm), leaf width (cm), number of leaves, foliar emission at 30, 60, 90, 105 days, after application and in harvest the weight of the cluster was determined in kg. A completely random block design was applied (DBCA) with five treatments and four repetitions, the separation between blocks was 2.5 meters between plants, each repetition was composed three rows of plants the side rows used as barriers and the middle row plants were used for data storage the crop's planting system was three bolillos with a planting distance of 2.5 meters between plants and 2.5 meters between rows. For the comparison of averages, the multiple range test was used Tukey (p<0.05). Among the most representative results obtained from the research was the height of the T3 treatment plant at 105 days with an average of 230.01 cm, perimeters of the pseudo-thalm the T3 at 105 days with 74.08 cm, leaf length the T3 with 210.87 cm, width of the leaf the T3 with 92.34 cm, number of leaves the T3 treatment with an average of 13.58 cm until the plant T3 averaged 4 leaves per month and in terms of harvesting the weight of the cluster the T3 had an average weight of 26,30 kg. This research shows that the use of translaminar fertilization as a complement in the productive system of the San Carlos de Chillovado hacienda is a feasible alternative. Keywords: Banana, Foliar Fertilization, Fertilizer Dose, Surfactant, Translaminar Product.